2008
DOI: 10.1016/j.rapm.2008.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound- or Nerve Stimulation-Guided Wrist Blocks for Carpal Tunnel Release: A Randomized Prospective Comparative Study

Abstract: This randomized prospective study demonstrates that ultrasound-guided wrist nerve blocks are as efficient as those performed with nerve stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…A total of 508 articles were rejected for the following reasons: 448 did not evaluate ultrasound-guided nerve blocks in surgical procedures, 30 were not RCTs, 24 did not compare ultrasound alone versus control, 5 did not assess upper or lower extremity single-shot nerve blocks, and one did not assess surgical success rate. Table 1 provides a detailed overview of the studies included in the analysis [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 508 articles were rejected for the following reasons: 448 did not evaluate ultrasound-guided nerve blocks in surgical procedures, 30 were not RCTs, 24 did not compare ultrasound alone versus control, 5 did not assess upper or lower extremity single-shot nerve blocks, and one did not assess surgical success rate. Table 1 provides a detailed overview of the studies included in the analysis [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 19 studies comparing US against other nerve location methods, 15 demonstrated significant benefit with US, whereas only 1 study favored PNS (Table 1). Commonly identified benefits of US included surrogates of block performance such as faster block performance time 4,6,8,10,13,14,16,18,20 and reduced number of needle passes 2,7,15 and surrogates of better quality block including faster sensory onset time 3,4,8,9,12Y14,16,20 and greater block success. 5,8,9,12Y14,16,20 It should be noted, however, that of the 8 studies that found faster block performance with US, 4 studies 6,13,16,20 did not include the US scan time required before needle insertion.…”
Section: Discussionmentioning
confidence: 99%
“…48 The only randomized controlled trial evaluating whether ultrasound or nerve stimulation is superior for wrist block performance in patients undergoing carpal tunnel surgery did not reveal any differences in success rate, but showed a shorter block performance time in the ultrasound group, whereas the nerve stimulation group had a faster onset time of complete sensory block. 49 …”
Section: Elbow Wrist and Digitalmentioning
confidence: 99%